Fabrication and characteristics of visible light active TiO2 films by reduction treatment in carbon powder. (1st July 2013) - Lu, Y; Hao, L; Matsuzaka, K; Pan, F; Yoshida, H
<x xml:space="preserve">Abstract</x> TiO2 film balls were fabricated by mechanical coating technique and the following high temperature oxidation, reduction reaction by carbon powder. The films were characterised by X-ray diffraction, SEM and electron probe microanalyser. X-ray diffraction revealed that rutile TiO2 films were formed during the oxidation and reserved in the following reduction reaction. Scanning electron microscopy results showed that the films had a composite microstructure of TiO2 and Ti films. After the reduction reaction, the films showed enhanced photocatalytic activity under ultraviolet (UV) or visible light irradiation. Absorption spectra analysis proved that the films' absorption spectra extended towards visible light. The balance of crystallinity and specific surface area is considered to be the main influencing factor of photocatalytic activity under UV light irradiation. The red shift of TiO2 films' absorption spectra due to the introduction of oxygen vacancy in the reduction reaction is believed to be the crucial reason of improving the visible light photocatalytic activity significantly.